2023
DOI: 10.1136/tc-2023-057958
|View full text |Cite
|
Sign up to set email alerts
|

Is the public ready for a tobacco-free Ireland? A national survey of public knowledge and attitudes to tobacco endgame in Ireland

Abstract: AimIreland will not meet the tobacco endgame goal set in its 2013 Tobacco-Free Ireland (TFI) policy of reducing smoking prevalence to less than 5% by 2025. Public opinion on tobacco endgame, a key lever to realise this goal, is uncharted in Ireland. This study aimed to measure public knowledge and attitudes to tobacco endgame.MethodsA telephone-administered cross-sectional survey of 1000 randomly dialled members of the general public was conducted in 2022. Prevalence of awareness, perceived achievability and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[55] Among the 47 included studies, 7 reported support estimates for an endgame goal. [21 27 31 38 46 49 50]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[55] Among the 47 included studies, 7 reported support estimates for an endgame goal. [21 27 31 38 46 49 50]…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies on product-focused policies, 14 related to mandating a VLNC standard for smoked tobacco products. [20 21 24 26 29 40 43 46 47 53 54 59-61] Among the six studies related to setting product standards to make products less appealing, five pertained to banning all additives,[20 21 23 29 30 46] and one to banning filters. [46] Only one study focused on a policy intended to promote the use of ‘clean’ nicotine products (e.g., e-cigarettes, nicotine gum, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations